SKIN AGING AND THE EFFECTS OF GLYCATION - Rodrigues Ferreira, Isabella (Health and Society, 2024)
Aging being a paradigm for aesthetic medicine nowadays, and with the concern to block or delay the aged appearance among people, with the increase in life expectancy and care, the progression of skin aging is considered a process irreversible, progressive and dynamic. However, it can be delayed with aesthetic and daily care such as the use of home care and adequate food. The poor diet performed due to stressful and agitated routines causes an influence on the acceleration of the skin aging process. It is taken into account that the consumption of foods rich in carbohydrates and fats provides the glycation process in a non-enzymatic way. The glycation process occurs between glucose and proteins, triggering end products such as advanced glycation (AGEs). Proteins with a half-life similar to that of collagen, are more susceptible to this process. In short, it is possible to verify that, according to the progress of the skin aging process, people seek to block or delay this physiological process even more, looking for aesthetic alternatives such as microneedling and food reeducation with diets low in carbohydrates and fat.